(untitled) (Observatorio Económico, 2016)
The current process of reform of the Chilean university education system raises several questions and impassioned debates. It is common to discuss free tuition by comparing, for example, Chile with Finland. Beyond how debatable such an association may be, it is also frequent—and more reasonable—to use the Argentine university system as a reference. Continue reading...